Low Doses of Lipopolysaccharide and Minimally Oxidized Low-Density Lipoprotein Cooperatively Activate Macrophages via Nuclear Factor κB and Activator Protein-1: Possible Mechanism for Acceleration of Atherosclerosis by Subclinical Endotoxemia - Wiesner, Philipp; Choi, Soo-Ho; Almazan, Felicidad; Benner, Christopher; Huang, Wendy; Diehl, Cody J.; Gonen, Ayelet; Butler, Susan; Witztum, Joseph L.; Glass, Christopher K.; Miller, Yury I. (Circulation research, 2010)
RATIONALE:Oxidized low-density lipoprotein (LDL) is an important determinant of inflammation in atherosclerotic lesions. It has also been documented that certain chronic infectious diseases, such as periodontitis and chlamydial infection, exacerbate clinical manifestations of atherosclerosis. In addition, low-level but persistent metabolic endotoxemia is often found in diabetic and obese subjects and is induced in mice fed a high-fat diet. OBJECTIVE:In this study, we examined cooperative macrophage activation by low levels of bacterial lipopolysaccharide (LPS) and by minimally oxidized LDL (mmLDL), as a model for subclinical endotoxemia-complicated atherosclerosis. METHODS AND RESULTS:We found that both in vitro and in vivo, mmLDL and LPS (Kdo2-LipidA) cooperatively activated macrophages to express proinflammatory cytokines Cxcl2 (MIP-2), Ccl3 (MIP-1α), and Ccl4 (MIP-1β). Importantly, the mmLDL and LPS cooperative effects were evident at a threshold LPS concentration (1 ng/mL) at which LPS alone induced only a limited macrophage response. Analyzing microarray data with a de novo motif discovery algorithm, we found that genes transcribed by promoters containing an activator protein (AP)-1 binding site were significantly upregulated by costimulation with mmLDL and LPS. In a nuclear factor–DNA binding assay, the cooperative effect of mmLDL and LPS costimulation on c-Jun and c-Fos DNA binding, but not on p65 or p50, was dependent on mmLDL-induced activation of extracellular signal-regulated kinase (ERK) 1/2. In addition, mmLDL induced c-Jun N-terminal kinase (JNK)-dependent derepression of AP-1 by removing nuclear receptor corepressor (NCoR) from the chemokine promoters. CONCLUSIONS:The cooperative engagement of AP-1 and nuclear factor (NF)-κB by mmLDL and LPS may constitute a mechanism of increased transcription of inflammatory cytokines within atherosclerotic lesions.